Volatile constituents of Eupatorieae (Asteraceae). Compositional multivariate analysis of volatile oils from Southern Brazilian species in the subtribe Disynaphiinae. (June 2021) - de Souza, Tiago J.T.; Bordignon, Sérgio A.L.; Apel, Miriam A.; Henriques, Amelia T.
Abstract: Volatile oils (VOs) obtained from the aerial parts of species from the Disynaphiinae subtribe (genera Acanthostyles, Campovassouria, Disynaphia, Grazielia, Raulinoreitzia, and Symphyopappus ) of Eupatorieae (Asteraceae) collected in Rio Grande do Sul, southern Brazil, were characterized using GC–MS. The yield of VOs relative to fresh material ranged from 0.2 to 1.7% between the Disynaphiinae subtribe samples ( Acanthostyles buniifolius, Campovassouria cruciata, Disynaphia ericoides, D. ligulifolia, D. spathulata, Symphyopappus casarettoi, S. reticulatus, S. itatiayensis, Grazielia gaudichaudieana, G. intermedia, G. nummularia, G. serrata, Raulinoreitzia crenulata, and R. tremula ). The VOs in this subtribe were mainly composed of terpene compounds. Compositional multivariate analysis demonstrated clustering between the samples of Grazielia and Raulinoreitzia on one side, which contain relatively higher proportions of monoterpenes, and Disynaphia and Campovassouria, which contain more oxygenated sesquiterpenes. The samples of Symphyopappus and Acanthostyles, which contain more sesquiterpene hydrocarbons, were located between these two main groups. Multivariate analysis accounting for the recent proposals of subtribal recircumscription of Eupatorieae was also performed. The odd chemistry of S. itatiayensis was in accordance with the recent attempts to exclude it from the genus Symphyopappus . Graphical abstract: Image 1 Highlights: The volatile chemistry of subtribe Disynaphiinae (Eupatorieae) was analyzed. Compositional PCA of Volatile Oils corroborates subtribal recircumscription. VO from Grazielia is characterized by hydrocarbon monoterpenes. VO from Disynaphia and Campovassouria are characterized by oxygenated sesquiterpenes. Symphyopappus itatiayensis and Raulinoreitzia tremula possess unique chemistry.